2017
DOI: 10.1902/jop.2016.160249
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Sampling Methods for Subgingival Plaque: Subgingival Paper Points or Mouthrinse Sample?

Abstract: There is no significant difference between MT4 and MSP for detection frequency of key pathogen A. actinomycetemcomitans. Key pathogens P. gingivalis, T. forsythia, T. denticola, P. micra, C. rectus, and E. nodatum show statistically higher detection frequencies with MT4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…To test the effect of periodontal treatment on salivary abundance of these periopathogens, we performed correlation analysis between salivary and subgingival levels of P. gingivalis , T. Forsythia , T. denticola , P. intermedia , P. micra , and F. alocis . Significant correlation on salivary and subgingival levels of P. gingivalis ( r = 0.60) and P. intermedia ( r = 0.78) was recorded at baseline, which agrees with previous cross‐sectional analysis, employing various contemporary methods for bacterial identification . Further, data demonstrated that salivary levels of periopathogens reflected subgingival alterations as an increase in correlation was noted from baseline to week 2 after periodontal treatment for all six periopathogens (Table ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To test the effect of periodontal treatment on salivary abundance of these periopathogens, we performed correlation analysis between salivary and subgingival levels of P. gingivalis , T. Forsythia , T. denticola , P. intermedia , P. micra , and F. alocis . Significant correlation on salivary and subgingival levels of P. gingivalis ( r = 0.60) and P. intermedia ( r = 0.78) was recorded at baseline, which agrees with previous cross‐sectional analysis, employing various contemporary methods for bacterial identification . Further, data demonstrated that salivary levels of periopathogens reflected subgingival alterations as an increase in correlation was noted from baseline to week 2 after periodontal treatment for all six periopathogens (Table ).…”
Section: Discussionsupporting
confidence: 88%
“…Primarily because of the ease and inexpensive nature of saliva sampling and analysis, saliva has been suggested as a substitute to local microbial sampling for monitoring of the oral microbiota . Differences in salivary bacterial profiles have been reported in patients with periodontitis compared to orally healthy controls, and several cross‐sectional studies have shown correlation between subgingival and salivary levels of specific periopathogens in periodontitis patients . However, red complex bacteria, that is, P. gingivalis, T. denticola , and T. forsythia , are also part of the tongue resident microbiota in orally healthy individuals, which is why salivary identification of periopathogens may not only reflect subgingival presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the majority of these bacterial species, including the proposed periopathogen P. gingivalis, were identified with higher relative abundance in patients with periodontitis. Salivary levels of P. gingivalis have been reported to associate with periodontitis (Damgaard et al, ), and previous studies have shown a positive correlation of salivary and subgingival levels of P. gingivalis (Belstrøm et al, ; Nickles, Scharf, Röllke, Dannewitz, & Eickholz, ) suggesting that the salivary microbiota reflects local bacterial alterations associated with periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…2 Doxycycline (DOX) acts on Gram-positive and Gram-negative bacteria and on specific periodontal pathogens. 3 Its main antibiotic mechanism of action is the inhibition of protein synthesis. 4 It presents anti-inflammatory properties through direct inhibition of the activity of matrix metalloproteinases, which participate in periodontal tissue destruction 5 and are considered to be the most potent anti-collagenase Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%